IMPLEMENTATION OF TRANSPORTATION METHODS IN OPTIMIZING THE DISTRIBUTION OF HIJAB PRODUCTS AT AYASHA HIJAB STORE - Robiatul Adawiya; Anriany Casanova; Mufida Awalia Putri; Muhammad Najib Mubarrok; Liansya Ayu Sariperkasi (State Islamic University of North Sumatra, 2022)
The problem of transportation costs is a problem faced by many companies, especially those that distribute goods from various places to various destinations, and Ayasha Hijab's company is no exception. The company has 3 stores and supplies Bella square veils from 3 different warehouses. This of course has an impact on the company's expenses considering the distance and the increasing number of requests. The researcher tries to find a solution by using the linear program transportation solution method. Researchers processed data from the Ayasha Hijab Company with the NWC model and then second processing to get optimal results with stepping stones and MODI. As a result, the optimal cost for the stepping stone and MODI models is IDR 5.125.000. The Stepping Stone and MODI methods get the optimal solution and can save costs around IDR. 3.350.000 from the NWC method with a cost of IDR. 8.475.000. Secondary data obtained from the calculation of